2005
DOI: 10.1093/chemse/bji073
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Odor Quality of Androstadienone During Exposure-Induced Sensitization

Abstract: Androstadienone is a steroid found in human sweat and other secretions. It has been widely proposed as a candidate for a human pheromone. As an odorant it possesses some unique properties. Here we demonstrate that, firstly, there is a very wide range of thresholds in the human population, and they are not normally distributed. Secondly, repetitive exposure causes a decrease in detection threshold of more than four orders of magnitude, and thirdly, accompanying this sensitization process is a change in the perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Their detection thresholds for the steroid were determined before and after training by a three alternative forced-choice test of a series of binary dilutions from a stock of 12.3 mM. Unlike many other odorants, thresholds for this steroid are not normally distributed in the general population (Jacob et al, 2006) necessitating nonparametric data analysis. The median detection thresholds were 0.22 and 0.32 mM for women (n ¼ 7) and men (n ¼ 7), respectively.…”
Section: Thresholdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their detection thresholds for the steroid were determined before and after training by a three alternative forced-choice test of a series of binary dilutions from a stock of 12.3 mM. Unlike many other odorants, thresholds for this steroid are not normally distributed in the general population (Jacob et al, 2006) necessitating nonparametric data analysis. The median detection thresholds were 0.22 and 0.32 mM for women (n ¼ 7) and men (n ¼ 7), respectively.…”
Section: Thresholdsmentioning
confidence: 99%
“…The induction of olfactory sensitivity in humans was initially restricted to androstenone but recently Jacob et al (2006) extended this to another, related steroid occurring in male (and to a lesser extent female) secretions, androstadienone. Dalton et al (2002) have studied the phenomenon with other unrelated, odorous compounds, and finding that repetitive testing resulted in greatly enhanced sensitivity to benzaldehyde and citralva, concluded that the induction of enhanced olfactory sensitivity was a more general phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…We know from the study of the inherited specific anosmia to androstenone that olfactory sensitivity may be dependent on the subjects' individual experience, in this case to repeated exposure to the chemical (Wysocki and Beauchamp 1984;Wysocki et al 1989). Such olfactory sensitivity changes were later confirmed for other compounds (Cain and Schmidt 2002;Dalton et al 2002;Jacob et al 2006). Furthermore, other frequently cited sources of variations of olfactory sensitivity are gender and age (Punter 1983).…”
Section: Introductionmentioning
confidence: 96%
“…General olfactory acuity declines with age [15,16] and is lower in men [17,18]. In contrast, odour-specific inter-individual differences have only been shown to be influenced by variability in the gene for an odorant receptor that is responsive to the odour [19-23] and by previous experience with the odour in question [24-27]. …”
Section: Introductionmentioning
confidence: 99%